Correctness of short cut fusion

From HaskellWiki
Revision as of 14:41, 6 July 2006 by Janis (talk | contribs) (commit additions)

Jump to: navigation, search

Short cut fusion

Short cut fusion allows elimination of intermediate data structures using rewrite rules that can also be performed automatically during compilation.

The two most popular instances are the foldr/build- and the destroy/unfoldr-rule for Haskell lists.

foldr/build

The foldr/build-rule eliminates intermediate lists produced by build and consumed by foldr, where these functions are defined as follows:

foldr :: (a -> b -> b) -> b -> [a] -> b
foldr c n []     = n
foldr c n (x:xs) = c x (foldr c n xs)

build :: (forall b. (a -> b -> b) -> b -> b) -> [a]
build g = g (:) []

Note the rank-2 polymorphic type of build.

The foldr/build-rule now means the following replacement for appropriately typed g, c, and n:

foldr c n (build g) <nowiki>&rarr;</nowiki> g c n

destroy/unfoldr

The destroy/unfoldr-rule eliminates intermediate lists produced by unfoldr and consumed by destroy, where these functions are defined as follows:

destroy :: (forall b. (b -> Maybe (a,b)) -> b -> c) -> [a] -> c
destroy g = g listpsi 

listpsi :: [a] -> Maybe (a,[a])
listpsi []     = Nothing
listpsi (x:xs) = Just (x,xs)

unfoldr :: (b -> Maybe (a,b)) -> b -> [a]
unfoldr p e = case p e of Nothing     -> []
                          Just (x,e') -> x:unfoldr p e'

Note the rank-2 polymorphic type of destroy.

The destroy/unfoldr-rule now means the following replacement for appropriately typed g, p, and e:

destroy g (unfoldr p e) <nowiki>&rarr;</nowiki> g p e

Correctness

If the foldr/build- and the destroy/unfoldr-rule are to be automatically performed during compilation, as is possible using GHC's RULES pragmas, we clearly want them to be equivalences. That is, the left- and right-hand sides should be semantically the same for each instance of either rule. Unfortunately, this is not so in Haskell.

We can distinguish two situations, depending on whether g is defined using seq or not.

In absence of seq

If g does not use seq, then the foldr/build-rule really is a semantic equivalence, that is, it holds that

foldr c n (build g) = g c n

The two sides are semantically interchangeable.

The destroy/unfoldr-rule, however, is not a semantic equivalence. To see this, consider the following instance:

g = \x y -> case x y of Just z -> 0
p = \x -> if x==0 then Just undefined else Nothing
e = 0

These values have appropriate types for being used in the destroy/unfoldr-rule. But with them, that rule's left-hand side "evaluates" as follows:

destroy g (unfoldr p e) = g listpsi (unfoldr p e)
                        = case listpsi (unfoldr p e) of Just z -> 0
                        = case listpsi (case p e of Nothing     -> []
                                                    Just (x,e') -> x:unfoldr p e') of Just z -> 0
                        = case listpsi (case Just undefined of Nothing     -> []
                                                               Just (x,e') -> x:unfoldr p e') of Just z -> 0
                        = undefined

while its right-hand side "evaluates" as follows:

g p e = case p e of Just z -> 0
      = case Just undefined of Just z -> 0
      = 0

Thus, by applying the destroy/unfoldr-rule, a nonterminating (or otherwise failing) program can be transformed into a safely terminating one. The obvious questions now are:

  1. Can the converse also happen, that is, can a safely terminating program be transformed into a failing one?
  2. Can a safely terminating program be transformed into another safely terminating one that gives a different value as result?

There is no formal proof yet, but strong evidence supporting the conjecture that the answer to both questions is "No!".

The conjecture goes that if g does not use seq, then the destroy/unfoldr-rule is a semantic approximation from left to right, that is, it holds that

destroy g (unfoldr p e) <math>\sqsubseteq</math> g p e

What is known is that semantic equivalence can be recovered here by putting moderate restrictions on p. More precisely, if g does not use seq and p is a strict function that never returns Just <math>\bot</math> (where \bot denotes any kind of failure or nontermination), then indeed:

destroy g (unfoldr p e) = g p e

In presence of seq

This is the more interesting setting, given that in Haskell there is no way to retrict the use of seq, so in any given program we must be prepared for the possibility that the g appearing in the foldr/build- or the destroy/unfoldr-rule is defined using seq.